The last runaway - Chevalier, Tracy (Dutton, 2013)
Forced to leave England and struggling with illness in the wake of a family tragedy, Quaker Honor Bright is forced to rely on strangers in the harsh landscape of 1850 Ohio and is compelled to join the Underground Railroad network to help runaway slaves escape to freedom.